2021
DOI: 10.5194/isprs-archives-xlvi-m-1-2021-677-2021
|View full text |Cite
|
Sign up to set email alerts
|

Use of Geographical Information System Approaches for the Diagnosis of San Isidoro Ruins (Madrid, Spain)

Abstract: Abstract. This article shows the application of different geoinformatic approaches for the diagnosis of a small hermitage located at the Spanish capital of Madrid. More specifically Structure from Motion photogrammetry for the 3D digitalization and orthophoto generation, and Geographical Information System (GIS) for uploading and management of the information were used. Both strategies were carried out using open-source software. In the case of the GIS approach the QGIS platform was chosen and some additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…• Un modelo 3D en base a la nube de puntos para su posterior uso en simulaciones computacionales por el método de los elementos finitos y metodologías HBIM. • El cartografiado exhaustivo de fases constructivas, materiales y lesiones a partir de las ortofotografías, obtenidas de la digitalización y apoyadas por fichas estandarizadas de lesiones y sistemas constructivos basadas en estudios anteriores de parte del equipo involucrado (Sedano Espejo et al, 2021). Maté González, C. Mayo Corrochano, D. Mencías Carrizosa y P. Villanueva Llauradó 2022, Universitat Politècnica de València…”
Section: Resultados Esperables Y Organización De La Información Generadaunclassified
“…• Un modelo 3D en base a la nube de puntos para su posterior uso en simulaciones computacionales por el método de los elementos finitos y metodologías HBIM. • El cartografiado exhaustivo de fases constructivas, materiales y lesiones a partir de las ortofotografías, obtenidas de la digitalización y apoyadas por fichas estandarizadas de lesiones y sistemas constructivos basadas en estudios anteriores de parte del equipo involucrado (Sedano Espejo et al, 2021). Maté González, C. Mayo Corrochano, D. Mencías Carrizosa y P. Villanueva Llauradó 2022, Universitat Politècnica de València…”
Section: Resultados Esperables Y Organización De La Información Generadaunclassified
“…Furthermore, historical and archaeological research has resulted in a repository of records which are directly linked in the platforms as documents, pictures and drawings. In most studies, particularly those reported in Section 3.4.1, where the 3D models are displayed as informative contents of a further host environment [67,[160][161][162]164,165,169], material and structural tests are also included. Differently, in the great majority of studies discussed in Section 3.4.2, where the 3D models are the main host environments, great attention is paid to some functions that might enhance the interaction with coloured point clouds, texturized polygonal meshes and resulting orthoimages beyond the basic functions of visualization, measurement and labelling through web-based commercial viewers.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some other studies were found, exploiting higher levels of customization and interoperability between models and tools. For instance, Sedano-Espejo et al [164] used the open source QGIS platform, further implemented with additional features, in order to collect relevant records on some archaeological ruins in Spain. The records refer to "construction materials and systems", "historical information", "damages" and "previous tests" and are all stored with their own field attributes in different shapefiles within the system.…”
Section: Informative Records Within Digital Host Environmentsmentioning
confidence: 99%
“…These aim at converting properties and information in qualitative and quantitative data, firstly, and then at structuring dependencies on descriptors and primary factors, according to thematic taxonomies derived from the glossary of decay stones (TG), existent ontologies for the geometric and semantic representation of urban and architectural entities (O), thematic normative for the recovery of cultural and landscape heritage (NR) and established approaches in recovery activities (AR). These factors and descriptors already include both geometric and semantic levels of details to be acquired or determined during the technical knowledge phase, allowing, for the data acquisition (e.g., archivist) or information (e.g., geometric data by means of ortho-images of direct surveys), traditional or innovative techniques (Sedano Espejo et al, 2021).…”
Section: State Of Art and Previous Experiencesmentioning
confidence: 99%